2015
DOI: 10.1371/journal.pone.0118293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Physical Inactivity in Community-Dwelling Older Adults in Ireland

Abstract: The public health challenges associated with rapid population ageing are likely to be exacerbated by poor physical activity levels. The purpose of this study was to identify correlates of physical inactivity in a population-representative sample of older adults in Ireland. This paper reports a secondary analysis of data from 4892 adults aged 60+ from the Irish Longitudinal Study on Ageing (TILDA). TILDA includes an assessment of the mental and physical health, and social and financial circumstances of particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 46 publications
10
54
5
1
Order By: Relevance
“…PASE evaluates leisure time activities, household and work-related activities, and because of different lifestyles in various societies, we have different results. The results showed that there was a significant relationship between ageing and physical activity decrease, the findings were in accordance with Salehi (15) and Dumith (36), and also in the Norliana et al (31) and Murtagh et al (35) studies. By aging, the amount of physical activity decreases, it is logical that by aging, the elderly have less regard for physical activity because of physiological and mental changes.…”
Section: Discussionsupporting
confidence: 88%
“…PASE evaluates leisure time activities, household and work-related activities, and because of different lifestyles in various societies, we have different results. The results showed that there was a significant relationship between ageing and physical activity decrease, the findings were in accordance with Salehi (15) and Dumith (36), and also in the Norliana et al (31) and Murtagh et al (35) studies. By aging, the amount of physical activity decreases, it is logical that by aging, the elderly have less regard for physical activity because of physiological and mental changes.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings of a positive association between self-rated health and physical activity level have been observed in cross-sectional studies with older adults in Ireland and Brazil. 2,23,26 In the present study, older adults who self-reported of having no fear of falling had higher level of physical activity. Those who were afraid of falling appeared to have loss of confidence, restriction of physical activities and social participation, physical frailty, and loss of independence.…”
Section: Comparison With Other Studiessupporting
confidence: 44%
“…Previous studies based in Europe, the US, and Japan, suggest that car ownership and use are positively correlated to the quality of life for the elderly (Chikaraishi, 2017;Hjorthol et al, 2010;Murtagh et al, 2015;Schmöcker et al, 2008;Schwanen et al, 2001). In part, this might mean that the elderly appreciate the freedom and independence afforded by cars and feel isolated and insignificant when they can no longer drive (Siren and Haustein, 2013).…”
Section: Discussionmentioning
confidence: 94%